Molding, patterning and driving liquids with light. (December 2021) - Lin, Feng; Quraishy, Aamir Nasir; Li, Runjia; Yang, Guang; Mohebinia, Mohammadjavad; Tong, Tian; Qiu, Yi; Vishal, Talari; Zhao, Junyi; Zhang, Wei; Zhong, Hong; Zhang, Hang; et al.
Graphical abstract: Abstract: When a laser beam induces surface tension gradient at the free surface of a liquid, a weak surface depression is expected and has been observed. Here we report giant depression and rupture in "optothermocapillary fluids" under the illumination of laser and sunlight. Computational fluid dynamics models were developed to understand the surface deformation and provided desirable physical parameters of the fluid for maximum deformation. New optothermocapillary fluids were created by mixing transparent lamp oil with different candle dyes. They can be cut open by sunlight and be patterned to different shapes and sizes using an ordinary laser show projector or a common laser pointer. Laser driving and elevation of optothermocapillary fluids, in addition to the manipulation of different droplets on their surface, were demonstrated as an efficient controlling method and platform for optofluidic operations. The fundamental understanding of light-induced giant depression and creation of new optothermocapillary fluids encourage the fundamental research and applications of optofluidics.